Factors that Determine Tourist Satisfaction and Tourists' Intention to Return to Tourist Destinations in Tarutung - Ria, Esther; Gumilang, Aulia; Andreas Hutahaean, Nathanael; Heriyati, Pantri (Universitas Trisakti, 2023)
The objective of this study is to elucidate the correlation between visitor satisfaction and the inclination to revisit. Furthermore, it encompasses supplementary factors such as perceived value, destination image, service quality, and accessibility. The research approach involved data collection using an online survey and sampling at the Tarutung tourist area, with a total of 203 respondents.The study's findings suggest that women make up the majority of tourists visiting the Tarutung tourism region. Furthermore, the tourists who visit are predominantly self-reliant individuals who do not depend on a travel agent. They tend to be between the ages of 25 and 30, which is commonly regarded as the prime working age. They can also be referred to as those who hold a bachelor's degree and have undergone formal schooling. Most of them are also making their first visit to the Tarutung tourism destination. By conducting data analysis, this research also concludes that there are two hypotheses that have a negligible effect. Insufficient evidence exists to indicate that the perception and ease of reaching a destination significantly affect tourist satisfaction. However, the three surviving theories were discovered to have a significant influence. Empirical evidence has demonstrated that both Perceived Value and Service Quality significantly influence tourist satisfaction in a positive manner. On the other hand, the level of satisfaction experienced by tourists also has a positive influence on their likelihood to visit again.